Decomposition rate and property changes of deadwood across an altitudinal gradient: a case study in the Babia Góra Massif, Poland - Adam Górski; Ewa Błońska; Jarosław Lasota (Scientific Reports)
Abstract The decomposition of deadwood is a key process in the biogeochemical cycle of forests, affecting water retention, soil structure and biodiversity. The aim of this study is to understand how the rate of deadwood decomposition changes depending on the location in the altitude gradient in mountain forest ecosystems. Additionally, the study investigates how the physical properties of wood vary with elevation. The experiment was conducted on the slopes of the Babia Góra Massif, where wood samples of four species (beech, fir, spruce, maple) were placed at three altitudes (800, 1000 and 1200 m above sea level). After 30 months, laboratory analyses were carried out on the density, porosity, mass loss and hydrophobicity of wood. In the case of coniferous wood (spruce and fir), the decomposition process proceeded at a similar rate across all altitudes, but more slowly compared to deciduous species. In contrast, hardwood decomposed more rapidly at lower altitudes, likely due to higher temperatures, greater microbial activity, and soil conditions more favorable to hardwood-decaying organisms. Wood decomposition led to a decrease in density and an increase in porosity, and hydrophobicity increased with altitude. The study provides new data on the dynamics of wood decomposition in the context of changing thermal and moisture conditions. The results can be used in conservation and management strategies for mountain forests.